Notes on the distribution and ecology of Aquilaria Lam. ( Thymelaeaceae) in Malaysia - Ibrahim, Faridah Hanum; Mustapa, Mohd Zamakshaury; Lepun, Philip; Tuan Ibrahim, Tuan Marina; Salleh @ Japri, Mohd Nazre; Alan, Ribka; Mohamed, Rozi (Forestry Department Peninsular Malaysia, 2009)
Gaharu is the resin produced from trees of the genus Aquilaria Lam. In Malaysia, there are five species of Aquilaria, viz. A. beccariana Van Tiegh, A. hirta Ridl., A. malaccensis Lam., A. microcarpa Baill. and A. rostrata Ridl. These species have been put by CITES in Appendix II which regulates trade in species that could potentially lead to extinction. A study was undertaken to re-examine the distribution and ecology of the different Aquilaria species in Malaysia. Besides generating data from field trips, additional data were obtained from the Fourth National Forest Inventory of Peninsular Malaysia (NFI 4). A total of 232 specimens had also been studied from the herbaria at Universiti Kebangsaan Malaysia (UKMB), Singapore Botanic Gardens (SING), University of Malaya (KLU), Forest Research Institute of Malaysia (KEP), Sarawak Forestry Department (SAR) and Sabah Forestry Department (SAN). The distribution of A. malaccensis which supplies the largest bulk of gaharu being traded locally and internationally is widespread in our Malaysian forests except the state of Perlis. The remaining species can be found from the primary lowland forest up to an altitude of 825m a.s.l. in various habitats. Information obtained on the distribution and ecology of Aquilaria species in Malaysia will be valuable to the State Forestry Departments for the conservation and management of these resources in the wild and also plantations.